2015
DOI: 10.1016/j.conbuildmat.2014.09.117
|View full text |Cite
|
Sign up to set email alerts
|

On entrained pore size distribution of foamed concrete

Abstract: 9The pore structure of foamed concrete is a significant characteristic since it affects properties 10 such as strength and durability. To investigate these properties, the determination of total air 11 voids content is not sufficient as the shape, size and distribution of air voids may also be

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 128 publications
(28 citation statements)
references
References 9 publications
1
27
0
Order By: Relevance
“…As stated in (Hilal et al 2015b), this matrix microstructure improvement can also be deduced from the difference between the vacuum saturation po- • Secondly, due to reduced size and connectivity of voids, by preventing their merging and producing a narrow void size distribution, inclusion of these additives achieved higher strength leading to brittle behaviour. In opposition to this, for all mixes, higher foam volume resulted in a greater degree of void merging, leading to large irregular voids which resulted in a wide distribution of void sizes and lower strength (Hilal et al 2015a); as a result a more ductile behaviour was noticed, i. e. the lower the density the higher the ductility. Compared to mixes without LWA, for a given density, inclusion of LWA leads to improved ductility with and without the other additives (i.e.…”
Section: Fracture Energy and Ductilitymentioning
confidence: 90%
“…As stated in (Hilal et al 2015b), this matrix microstructure improvement can also be deduced from the difference between the vacuum saturation po- • Secondly, due to reduced size and connectivity of voids, by preventing their merging and producing a narrow void size distribution, inclusion of these additives achieved higher strength leading to brittle behaviour. In opposition to this, for all mixes, higher foam volume resulted in a greater degree of void merging, leading to large irregular voids which resulted in a wide distribution of void sizes and lower strength (Hilal et al 2015a); as a result a more ductile behaviour was noticed, i. e. the lower the density the higher the ductility. Compared to mixes without LWA, for a given density, inclusion of LWA leads to improved ductility with and without the other additives (i.e.…”
Section: Fracture Energy and Ductilitymentioning
confidence: 90%
“…Paste consistency could be adjusted by adding a water reducer. Meanwhile, Hilal et al [19,20] analyzed the coupling relationship between bubbles under natural and stress states during foam concrete coagulation and pores in hardened foam concrete. The scholars found that the bubbles combined during the stirring and coagulation of foam concrete, thereby expanding the pore diameter distribution of the foam concrete and reducing the foam concrete's strength.…”
Section: Introductionmentioning
confidence: 99%
“…Like other types of concrete [9][10][11], the material properties of foamed concrete are significantly affected by the pore characteristics, and many studies have been reported about the pore characteristics of foamed concrete over the past few years. Kearsley and Wainwright [12] examined the porosity effect on the mechanical property of foamed concrete, and Hilal et al [13] investigated the size distribution of the entrained pores in foamed concrete. Wei et al [14,15] characterized and simulated the microstructure of foamed concrete.…”
Section: Introductionmentioning
confidence: 99%